THE EFFECT OF ENVIRONMENTAL MANAGEMENT ACCOUNTING ON ENVIRONMENTAL COST EFFICIENCY AND PROFITABILITY: A SYSTEMATIC LITERATURE REVIEW - Zahrani, Olivia Putri; Sari, Rela (LP2M IBK Nitro, 2025)
This study aims to analyze the effect of EMA on environmental cost efficiency and corporate profitability in Indonesia through the Systematic Literature Review (SLR) approach. This study examines 30 scientific articles from journals indexed by Scopus (Q1 & Q2) and Sinta (minimum Sinta 4) to obtain a comprehensive picture of research trends, key findings, and challenges faced in implementing EMA in various industrial sectors. The results of the study indicate that the implementation of EMA has a positive impact on environmental cost efficiency, especially in terms of waste reduction, energy efficiency, and optimization of more environmentally friendly production processes. Through more accurate recording and reporting of resource use and environmental impacts, EMA allows companies to identify areas that need improvement so that they can reduce environmental-related operational costs. In addition, several studies have shown that companies that implement EMA tend to have higher levels of profitability than companies that have not implemented it. This is due to increased efficiency in resource management, reduced environmental tax burdens, and a better corporate image in the eyes of stakeholders. The implications of this study emphasize the importance of policies that support the implementation of EMA in the industrial sector, both through government incentives and increased regulations that require environmental accounting reporting. This study also provides insights for academics and practitioners regarding the role of EMA in improving operational efficiency and business sustainability of companies. With the integration of business strategy and environmental approach based on EMA, it is expected that companies in Indonesia can achieve a balance between economic growth and environmental sustainability.